Optimalisasi Keselamatan Pengguna Jalan Melalui Program Pembuatan Rambu Jalan Di Desa Pasar Ngalam, Kecamatan Air Periukan, Kabupaten Seluma - Dirgo Hafiizh Danil; Khotimah Wahdaniyah; Melly Jayanti; Maudya Ramadhani; Marchell Febrian. G; Arifah Nur Fitriani; Panugra Kardiansya; Afri Melda; Dimas Aditya; Muhammad Naufal Aditya Lubis (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The road signage installation program in Pasar Ngalam Village, Air Periukan District, Seluma Regency, was implemented as a strategic effort to enhance road user safety in a rural area that previously lacked adequate road infrastructure. This study aims to analyze the program's effectiveness in improving traffic safety and to identify the factors facilitating or hindering its implementation. The results indicate that the program successfully raised community awareness regarding the importance of traffic safety, reduced the risk of accidents at accident-prone locations, and improved access to navigational information for both residents and visitors.